Eumasia thomasii sp. nov. a new species of the subfamily Eumasiinae (Lepidoptera: Psychidae) from India - Unnikrishnan, Usha Ayyath; Sobczyk, Thomas; Jose, Roby Thekkudan; Jose, Joyce (Zootaxa, 2022)
A new species of bagworm, Eumasia thomasii sp. nov. is described from Kerala, India. This is the third species in the genus Eumasia reported from India and the tenth from Asia. The report presents the morphology of adults, larva, and cases along with information on distribution and ecology.